Impact of changes in the real effective exchange rate on the competitiveness of agriculture products - Law, Li Chen (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The objective of this paper is to investigate the impact of Real Effective Exchange Rate (REER) on the export performance of Malaysia agriculture products. Beside the Real Effective Exchange Rate (REER), other factors are also taken into consideration, which are Malaysia’s Gross Domestic Product (GDP) per capita, trade openness, financial openness, and the main trading partners’ bilateral distance. The econometric methods employed in this study include the Im, Pesaran and Shin (IPS) Test, Maddala and Wu (MW) Test, Pedroni Test and Dynamic OLS (DOLS) estimator Test. Based on the data covering the period of 30 years (1981 – 2011), the results suggest that no association is found between real effective exchange rate (REER) and the export of agriculture products. However, positive association is found between the real GDP per capita of the country and the agriculture export. For the trade and financial openness, the increase of trade openness will have negative impact of agriculture export, while financial openness also does not show any impact or relationship to agriculture export.